An ANP (Analytic Network Process)-based Multi-Criteria Decision Approach for The Selection of Sugar-Cane Industry Development - Ferizandi Qauzar Gani; Ridho Hantoro (Institut Teknologi Sepuluh Nopember, 2018)
Acknowledging the issue of energy sustainability, the sugar industry has begun to look at plans to sell electricity to address energy sustainability issues. A scenario with the potential to sell excess electricity motivates this research to analyze the strategies of the sugar industry development. In such situations an ANP approach is applied for the selection of appropriate strategies. This study analyzes the potential for electricity sales in two alternative plant development strategies of three sugarcane industries which from the results, Strategy A (cogeneration scheme) allows to sell electricity for 223-293 days while strategy B (independent power plant scheme) allows to sell throughout the year. The result also shows that by using ANP, it is found that strategy A is better than strategy B